Roadmap of Scanning Probe Microscopy - Morita, Seizo.; Morita, Seizo. (NanoScience and Technology,, 2007)
Scanning tunneling microscopy - with its applications that span not only atomic resolution but also scanning tunneling spectroscopy, atom/molecule manipulation and nanostructuring, and inelastic electron tunneling spectroscopy - has achieved remarkable progress and become the key technology for surface science. Besides, atomic force microscopy is also rapidly developing and achieving remarkable progress and accomplishments such as true atomic resolution, atom/molecule identification, manipulation and nanostructuring. This book that predicts the future development for all of scanning probe microscopy (SPM). Such forecasts may help to determine the course ultimately to be taken and to accelerate research and development on nanotechnology and nanoscience, as well as all SPM-related fields in future.